2013
DOI: 10.1186/1471-2393-13-134
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of men on antenatal and delivery care service utilisation in rural western Kenya: a qualitative study

Abstract: BackgroundPoor utilisation of facility-based antenatal and delivery care services in Kenya hampers reduction of maternal mortality. Studies suggest that the participation of men in antenatal and delivery care is associated with better health care seeking behaviour, yet many reproductive health programs do not facilitate their involvement. This qualitative study conducted in rural Western Kenya, explored men’s perceptions of antenatal and delivery care services and identified factors that facilitated or constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
160
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(201 citation statements)
references
References 34 publications
(41 reference statements)
32
160
2
7
Order By: Relevance
“…Engagement of male partners is particularly important in this setting where men have strong fertility desires and influence over reproductive decision-making (Crankshaw et al, 2012). Moreover, the participation of men in antenatal care is associated with better health seeking behavior (Kwambai et al, 2013) and better reproductive health outcomes (Aluisio et al, 2011; Mullany, Becker, & Hindin, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Engagement of male partners is particularly important in this setting where men have strong fertility desires and influence over reproductive decision-making (Crankshaw et al, 2012). Moreover, the participation of men in antenatal care is associated with better health seeking behavior (Kwambai et al, 2013) and better reproductive health outcomes (Aluisio et al, 2011; Mullany, Becker, & Hindin, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…As shown in a study in Asembo Kenya some men view male involvement in delivery issues as less important compared to striving to achieve economic wellbeing of the family 12 . Women perceiving child birth as a women affair that does not require male partner involvement may contribute to low male partner involvement as established by 18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in Nyandarua Kenya, 58.4% of the women interviewed had their place of delivery decided by their husbands 11 . While a study at Asembo Kenya revealed that majority of the women (87%) made decisions on delivery site on their own 12 . Despite the positive contributions of male involvement in tackling maternal mortality and morbidity, little is known on their level of involvement in this study area.…”
mentioning
confidence: 99%
“…1 Men cite numerous barriers for partner HIV testing at antenatal clinics, including the belief that antenatal care is a woman's activity and that it is not culturally appropriate as a man to be involved in these visits, as well as not feeling welcome in the clinic. 1522 …”
Section: Introductionmentioning
confidence: 99%